A prospective clinical trial evaluating the safety and efficacy of the combination of rituximab and plerixafor as a mobilization regimen for patients with lymphoma. Issue 1 (25th May 2012) - Kaufman, Jonathan L.; Flowers, Christopher R.; Rados, Karen D.; Calandra, Gary B.; Vose, Julie M.; Hewes, L. Becker; Lonial, Sagar; Langston, Amelia A.; Khoury, H. Jean; Lechowicz, Mary Jo; Waller, Edmund K.
<x xml:space="preserve">Abstract</x> BACKGROUND: Previous reports suggested that rituximab may impair stem cell collection and posttransplant engraftment in lymphoma patients undergoing autologous hematopoietic progenitor cell transplantation. STUDY DESIGN AND METHODS: A prospective biologic allocation study examined the effect of adding rituximab to a mobilization regimen of plerixafor and granulocyte–colony‐stimulating factor (G‐CSF) for patients with CD20+ lymphoma compared with CD20− lymphoma patients mobilized without rituximab. The primary endpoint was safety of the rituximab‐containing regimen; secondary endpoints compared the efficiency of stem cell collection, posttransplant engraftment, graft characteristics, mobilization kinetics, immune reconstitution, and engraftment durability between the cohorts of patients with CD20+ and CD20− lymphoma. RESULTS: Fifteen subjects assigned to each treatment arm were accrued. Both mobilization regimens had similar toxicities. The median number of CD34+ cells collected (7.4 × 106/kg vs. 6.4 × 106/kg) and the median numbers of days of apheresis needed to collect stem cells were not different between the CD20+ and CD20− cohorts. No significant differences in neutrophil engraftment (median, 13.5 days vs. 13 days) or platelet engraftment (22 vs. 21 days) or in graft durability were seen comparing patients with CD20+ versus CD20− lymphoma. There were no significant differences in the kinetics of blood T‐cell or natural killer–cell reconstitution comparing the two groups. B‐cell reconstitution was delayed in the CD20+ lymphoma group, but this did not translate into a significant increase in infectious complications. CONCLUSION: Rituximab can be safely added to the combination of plerixafor and G‐CSF as a mobilization strategy without excess toxicity or posttransplant engraftment delays for patients with chemosensitive lymphoma undergoing autologous hematopoietic progenitor cell transplantation.